Effect of Garlic as a Spice on Salt Preferences of Hypertensive Individuals - Nugrahani, Gardinia; Afifah, Diana Nur (Pakistan Journal of Nutrition, 2016)
Hypertension can be affected by dietary habits, such as consumption of excessive salt or foods with a high salt content. In some foods the addition of spices can lower the need for salt to maintain flavor. Moreover, the use of garlic as a spice has been shown to have anti-hypertensive effects. This study examined the effect of garlic as a spice on salt preferences of hypertensive individuals. A total of 44 hypertensive subjects were classified into two groups, a control group (n = 22) and treatment group (n = 22). Both groups were first asked to determine their preference for food samples with three different salt concentrations (0.25, 0.50 and 0.75%). Ten minutes later the two groups tasted food samples with the same salt concentrations, but garlic was added to the samples given to the treatment group. Both groups had similar physical and dietary characteristics before the treatment (p>0.05). Salt preferences changed from the high concentration (0.75%) to lower concentration (0.25 and 0.05%) samples for the control group (18.2%), but a higher percentage of the treatment group (31.8%) preferred the lower salt food samples when garlic was added, although this result did not reach levels of significance (p>0.05). These results suggest that the addition of spices such as garlic to foods may alter salt concentration preferences and promote consumption of foods with lower salt contents.